The effects of environmental innovations and international technology spillovers on industrial and energy sector emissions – Evidence from small open economies - Alola, Andrew Adewale; Rahko, Jaana (Elsevier, 2023)
Environmental innovations hold promise for cutting greenhouse gas (GHG) emissions, but most technology investments are made in large technologically leading countries. Thus, emission reductions in small open economies, such as the Nordic countries, depend on not only domestic technological development, but also technology spillovers from foreign countries. The present study analysed how the development of climate change technologies affected the Nordic countries' GHG emissions from the industrial and energy sectors during a particular time frame. Consequently, while controlling for economic growth and population, domestic and foreign technological development's effects on industrial and energy sector GHG emissions were examined from the 1990–2019 period. The results revealed that both domestically developed environmental technologies and technology spillovers from foreign economies mitigated GHG emissions from these nations' energy and industrial sectors, thereby providing an efficient pathway to achieving sectoral environmental sustainability. In particular, domestic environmental technologies were found to be more efficient in driving environmental sustainability in the industrial sector, whereas impacts from domestic and foreign technological development did not differ significantly in the energy sector. Furthermore, given that economic growth plays a vital role in GHG emissions, environmental Kuznets curve (EKC; inverted U-shaped and U-shaped) relationships have been observed in the energy and industrial sectors, respectively. This suggests that the examined countries' industrial sectors have more environmental quality hurdles to overcome.
Keywords: Environmental technologies; Diffusion of technology; Nordics; emissions; greenhouse gases; environmental technology; fi=Taloustiede|en=Economics|